Renewing the Future: Social Innovation Systems, Sector Shift, and Innoweave - Stephen Huddart (Technology Innovation Management Review, 2012)
Against a backdrop of various “occupy” movements signifying civic dissatisfaction with the social contract, and in an era of fiscal restraint affecting governments and communities in many parts of the world, we need new and more effective ways to address complex social challenges. While continuous innovation is commonly understood to be a source of growth, productivity improvement, and competitive advantage in the technology and manufacturing sectors, the author’s focus is on social innovation systems, designed to replace maladaptive institutions and obsolete policy frameworks with novel and disruptive means for improving outcomes on issues such as population health and climate change. This article proposes a definition of such systems, and examines how system-level tools including impact investing, open data platforms, and “change labs” are fostering collaboration among the private, public, and community sectors. We argue that a key priority at this time is to make these and other tools and processes for social innovation available to community organizations and their government and business partners everywhere, in a manner that allows for continuous cycles of implementation and learning. The author describes one such project currently being developed in Canada by Social Innovation Generation and other partners, called Innoweave. Innoweave is a technology-enabled social innovation system for sharing the tools and processes of social innovation with the community sector. The article concludes with a call for multi-sectoral participation in social innovation systems as an investment in society’s adaptive capacity and future wellbeing.